Overlapping and fragmentation in the protection and conservation of the marine environment in areas beyond national jurisdiction - Ardito, Giovanni; Andreone, Gemma; Rovere, Marzia (Frontiers in Marine Science, 2023)
Marine areas beyond national jurisdiction (ABNJ) are under the growing threat of cumulative anthropogenic impacts including fishing, shipping, energy extraction, certain forms of marine scientific research, and the imminent deep seabed mining that prefigure a critical scenario in terms of biodiversity loss and environmental degradation. This article offers a contribution to the discussion on the best approaches to effectively implement environmental protection and conservation in ABNJ, also in the light of ongoing intergovernmental negotiations on the conclusion of an agreement implementing the United Nations Convention on the Law of the Sea on the conservation and sustainable use of biological diversity in ABNJ. The paper first analyzes the current legal gaps in the protection and conservation of ABNJ and the tools developed by some regional and universal regimes to preserve vulnerable marine ecosystems. It then presents two case studies, relating to hydrothermal vent fields of the Mid Atlantic Ridge (Lost City) and the South-West Indian Ridge (Longqi field) to discuss the fragmentation of the legal regimes applicable to ABNJ as well as the difficult cooperation among the regional, global and sectoral frameworks involved in their governance. The case studies show that a coordination mechanism, based on mutual recognition of the protection and conservation measures taken by each competent organization in a specific field, is of utmost urgency. Only a more structured system of cooperation among States and international organizations, that the new implementation agreement will hopefully develop, will allow for the identification of the most appropriate tools for the protection of a given marine area from the cumulative impacts of human activities.